Upaya Mahasiswa Membentengi Generasi Muda dari Ancaman Narkoba Konvensional dan NPS Melalui Tindakan Preventif di Perumahan Griya Hasanah Cikarang Barat - Inna Nisawati Mardiani; Astrian Hessy Defitri; Hangudi Pangasta; Kurnia Sandy; Rima Indah Sari; Ribka Marpaung (STIKes Ibnu Sina Ajibarang, 2024)
Due to the rising number of drug misuse cases in Indonesia, we students are involved in preventive initiatives as a means of safeguarding the next generation. In order to help raise awareness, knowledge, and prevent drug abuse among adolescents, as well as to encourage changes in adolescent behavior to be more cautious and avoid involvement in drug use, the activity with the theme